The effectiveness of ozone therapy in the treatment of peri-implantitis - Dzhafarova, Айят Рафиг; Abbasova, Есміра Мірахмед (Actual Dentistry, 2022)
Abstract. For the prevention of complications in the post-operative period, various drugs of general and local effect are used, in particular, antiseptics, antibiotics and drugs of the sulfonamide series, traditionally used in dental practice after any outpatient surgery. At the same time, as experience shows, these measures are not always effective, which keeps the frequency of complications after dental implantation at a fairly high level. Therefore, the issue of further development of physiotherapy methods aimed at compensating microcirculatory disorders and strengthening regenerative and reparative processes that contribute to the strengthening of implants is still acute. In recent years, for the prevention of surgical complications in dentistry, various methods of modern physiotherapy, which have a sufficiently pronounced anti-inflammatory, analgesic and regenerative effect, have become more widely used, but these effects are not considered to be sufficiently effective in all cases. The specified circumstances significantly actualize the search and development of new, more effective physiotherapeutic methods of correction of early complications of dental implantation, pushing them to the forefront of the priority scientific and practical tasks of modern medicine. This circum stance determined the main content of this study.